Distress, concerns and unmet needs in survivors of head and neck cancer: a cross‐sectional survey. (7th August 2015) - Wells, M.; Cunningham, M.; Lang, H.; Swartzman, S.; Philp, J.; Taylor, L.; Thomson, J.
<x xml:space="preserve">Abstract</x> The aim of this study was to identify the distress, unmet needs and concerns of head and neck cancer (HNC) survivors in the first 5 years after treatment. Two hundred and eighty HNC survivors from three Scottish health boards responded to a cross‐sectional postal survey in 2011. Questionnaires included the Distress Thermometer, Patient Concerns Inventory (PCI) and an adapted version of the PCI to measure unmet needs. One‐third of the survivors had moderate or severe levels of distress, and 74% had at least one unmet need. The most common concerns and unmet needs included oral and eating problems, fear of recurrence and fatigue. Multivariate analysis revealed that being younger, out of work (not retired), ever having had a feeding tube fitted, having a greater number of comorbidities and living alone were associated with higher levels of distress, concerns and unmet needs. The diversity of concerns and unmet needs identified in this study highlights the importance of holistic needs assessment as part of follow‐up care for HNC survivors with tailoring of support for particular concerns. Specific information resources and self‐management strategies are required to help HNC survivors with the practical and functional consequences of HNC treatment.